Debate: Preventive coronary intervention for vulnerable plaque. The clinical cardiologist’s approach - Rosa Fernández-Olmo (REC: Interventional Cardiology (English Ed.))
QUESTION: We would like to know your interpretation of the PREVENT trial.1 Do you think it could change clinical practice regarding the treatment of vulnerable plaques? ANSWER: The PREVENT1 is an open-label clinical trial comparing coronary intervention plus optimal medical therapy versus optimal medical treatment alone in patients with high-risk vulnerable plaques without flow limitation. In the group undergoing coronary intervention combined with optimal medical therapy, this trial demonstrated a 46% relative risk reduction (odds ratio, 0.54; 95% confidence interval [95%CI], 0.33-0.87; P = .0097) for the primary endpoint—a composite of cardiac death, target vessel myocardial infarction, ischemia-driven target vessel revascularization, or hospitalization due to unstable or progressive angina—2 years after randomization. Furthermore, this effect was maintained in each component of the primary endpoint, and during the study follow-up. Although current clinical practice guidelines do not indicate coronary intervention for this type of lesion, this trial paves the way for reflection on several aspects. We could argue that what this trial is truly analyzing is a focal preventive treatment of vulnerable plaque—which, by current definition, is what is being done—or if this approach should be considered a true focal treatment, if we consider vulnerable plaque as a “diseased plaque.” Until now, interventional treatment...